Correlation of Corneoscleral Membrane Biomechanical Properties and Eye Morphometric Parameters in Patients with Primary Open-Angle Glaucoma - B. M. Aznabaev; A. Sh. Zagidullina; I. A. Lakman; R. R. Islamova; R. R. Sattarova (Oftalʹmologiâ)
Purpose: to study a correlation between morphometric parameters of the eye and tonometry data, taking into account viscoelastic properties of the cornea in patients with primary open-angle glaucoma (POAG), as well as in practically healthy individuals using different methods of tonometry. Patients and Methods. Correlations between morphometric parameters of the eye and tonometry data were studied in view of viscoelastic properties of the cornea in 51 patients with POAG who were observed at the “Optimed” Laser Vision Recovery Center in Ufa (99 eyes) and in 31 practically healthy individuals (62 eyes). Various methods of tonometry were used: tonometry according to Maklakov, contactless tonometry, tonometry with the Ocular Response Analyzer (ORA, Reichert Inc., USA), as well as ultrasound echobiometry, pachymetry. Results. The CH and CRF parameters reflecting the biomechanical properties of the corneoscleral membrane of the eye were close in value to each other with a high degree of positive correlation in the control group (ρ = 0.783, p < 0.001), with an average correlation in the group with POAG (ρ = 0.545, p < 0.001). In eyes with POAG, a negative CH correlation of average degree with corneal-compensated IOP (ρ = -0.572, p < 0.001), a negative CRF correlation of moderate degree with IOP by the Maklakov method (ρ = -0.346, p < 0.001) and corneal-compensated IOP with dynamic bi-directional applanation tonometry (ρ = -0.327, p = 0.001), low correlation with IOP using contactless tonometry (ρ = 0.243, p < 0.015) were observed. In the group of patients with POAG, a positive average correlation was found between the central thickness of the cornea and CRF (ρ = 0.398, p < 0.001), and CH (ρ = 0.368, p < 0.001), low correlation with IOP using contactless tonometry (ρ = 0.266, p = 0.008). Conclusion. Correlations of biomechanical properties of the corneoscleral membrane and morphometric parameters of the eye in patients with POAG were revealed using different methods of tonometry. In the group of patients with POAG and in the control group, positive correlations of the central thickness of the cornea with the IOP level in tonometry were determined by the contactless method, as well as with the main ORA parameters reflecting the visco-elastic properties of the fibrous membrane of the eye — the corneal resistance factor, corneal hysteresis.